Equations of dynamic and static problems of nonhomogeneous and anisotropic elastic layered-composite plates - Toan, Pham Thi (Vietnam Journal of Mechanics, 1996)
The homogenization method for studying composite materials had been introduced in [1]. By this method the problem of nonhomogeneous and anisotropic elastic layered w composite material reduces to the set of problems of homogeneous, anisotropic elastic material. In this paper the governing equations of dynamic and static problems of layered - composite plates are formulated. An example is considered, obtained results can be compared with ones of multi-layered plate method.